The effect of soaking heat-polymerized acrylic resin denture base in avocado seed extract (Persea americana Mill.) on the inhibition of denture-plaque microorganisms biofilm growth [version 2; peer review: 1 approved, 2 approved with reservations, 1 not approved] - Siti Wahyuni; Thalia Angela; Susanna Halim (F1000Research)
Background Heat polymerized acrylic (HPA) resins are known to have high porosity that contributes to increased surface roughness and microcrack formation in stress areas. This facilitates the attachment and growth of polymicrobial biofilms contributing to increased antimicrobial resistance. Many research had been carried out on avocado seeds, but no research that studies avocado seeds effect on denture-plaque microorganism biofilm on HPA resin has been found. Methods This study used 144 samples (n=144), namely HPA resin discs covered with mono-species and polymicrobial biofilms. The discs were soaked for 8 hours in the 5%, 10%, 15%, 20% avocado seed extract, positive control (alkaline peroxide), and negative control (aquadest). Each disc was shaken with a vortex mixer for 1 minute, and 100 μL was added into 96-well microplates with three times repetition and incubated for 24 hours. A microtiter plate biofilm formation assay was then conducted The inhibition values were determined from the percentage inhibition value formula which required absorption values from a microplate reader (595 nm). The research data were analyzed using a univariant test, and a one-way ANOVA test, accompanied by Welch ANOVA on non-homogenous data. Results In this research, it was found that the MBIC50 of avocado seed extract against the mono-species of C. albicans (5%), C. glabrata (5%), A. odontolyticus (15%), S. gordonii (15%), S. aureus (10%), while against polymicrobial was 20%. There was a significant effect of soaking HPA resin in avocado seed extract on the inhibition of mono-species and polymicrobial biofilms with a value of p<0.001 (p<0.05). Conclusion The MBIC50 of avocado seed extract in polymicrobial biofilm group was higher than that in the mono-species biofilm groups. Although alkaline peroxide showed higher inhibition value than that of the MBIC50 in polymicrobial biofilm group, 20% avocado seed extract was concluded effective as it inhibited >50% polymicrobial biofilm.